Concurrent validity and exploratory factor analysis of the malay version of Center for epidemiologic studies-depression Scale (cesd) among Malaysian adolescents - Siti Raudzah, Ghazali; Ask, Elklit; Rekaya Vincent, Balang; Chen, Yoke Yong (ASEAN federation of Psychiatry and Mental Health, 2016)
Objectives: The objective of this study is to validate the Malay version of the Centre for Epidemiologic Studies-Depression scale (CESD) among adolescents. Methods: Nine hundred and thirty-one adolescents completed the Malay version of CESD and Hopkins Symptom Checklist-depression scale (HSCL-depression). Results: Results showed that the internal consistency of both the scale as a whole and the subscales was highly consistent. The concurrent validity was established by examining the relationship between CESD with the HSCL-depression scale. It showed a significant correlation between the two scales. The factor structure was similar to that observed in previous studies in other samples. Three factors were extracted, which accounted for 48.4% of the variance: a depressive affect factor; a positive affect factor and somatic symptoms factor which were combined with interpersonal items. Conclusion: The Malay version of CESD with 20 items has satisfactory psychometric properties and can be used for Malaysian adolescents.